RETRACTED: Postharvest Processing and Characteristics of Ateng Super Arabica Coffee Cultivar - Mulyani, Putri; Mahfut, Dwi; Akpertey, Abraham; Piato, Kevin (Review of Education, Science, and Technology, 2025)
RETRACTION NOTICE This article has been formally retracted by the Editorial Board following a confirmed case of authorship fraud.  An individual listed as a co-author formally notified the journal that he did not author, contribute to, or approve the submission of this manuscript. His name and institutional affiliation were used without authorization. Following internal review, the Editorial Board determined that the submission involved fraudulent misrepresentation of authorship, constituting a serious breach of publication ethics. The article has been retracted to preserve the integrity of the scholarly record. The original content has been removed from public access.